Cell death induction and protection by activation of ubiquitously expressed anion/cation channels. Part 3: the roles and properties of TRPM2 and TRPM7 - Okada, Yasunobu; Numata, Tomohiro; Sabirov, Ravshan Z.; Kashio, Makiko; Merzlyak, Peter G.; Sato-Numata, Kaori (Frontiers in Cell and Developmental Biology, 2023)
Cell volume regulation (CVR) is a prerequisite for animal cells to survive and fulfill their functions. CVR dysfunction is essentially involved in the induction of cell death. In fact, sustained normotonic cell swelling and shrinkage are associated with necrosis and apoptosis, and thus called the necrotic volume increase (NVI) and the apoptotic volume decrease (AVD), respectively. Since a number of ubiquitously expressed ion channels are involved in the CVR processes, these volume-regulatory ion channels are also implicated in the NVI and AVD events. In Part 1 and Part 2 of this series of review articles, we described the roles of swelling-activated anion channels called VSOR or VRAC and acid-activated anion channels called ASOR or PAC in CVR and cell death processes. Here, Part 3 focuses on therein roles of Ca 2+ -permeable non-selective TRPM2 and TRPM7 cation channels activated by stress. First, we summarize their phenotypic properties and molecular structure. Second, we describe their roles in CVR. Since cell death induction is tightly coupled to dysfunction of CVR, third, we focus on their participation in the induction of or protection against cell death under oxidative, acidotoxic, excitotoxic, and ischemic conditions. In this regard, we pay attention to the sensitivity of TRPM2 and TRPM7 to a variety of stress as well as to their capability to physicall and functionally interact with other volume-related channels and membrane enzymes. Also, we summarize a large number of reports hitherto published in which TRPM2 and TRPM7 channels are shown to be involved in cell death associated with a variety of diseases or disorders, in some cases as double-edged swords. Lastly, we attempt to describe how TRPM2 and TRPM7 are organized in the ionic mechanisms leading to cell death induction and protection.